Surgical Correction of Inguinal Hernias in Children Using Minimally Invasive PIRS Method - A.Y. Nakonechnyi; A.S. Kuzyk; R.A. Nakonechnyi (Zaslavsky O.Yu., 2016)
Introduction. Inguinal hernia (IH) - one of the most common childhood diseases that requires surgical treatment. The main indication for surgical treatment of IH is a risk of its strangulation. Among the methods of laparoscopic herniorrhaphy, PIRS (percutaneous internal ring suturing) is especially promising one. Objective of the study - to analyze our own clinical material of surgical treatment for IH in children using PIRS. Materials and methods. The study included 62 children with IH aged 2 months to 7 years, who were operated in 2012-2015 using PIRS method with suturing the internal inguinal ring. Among patients, there were 48 (77.4 %) boys and 14 (22.6 %) girls. Right-sided hernia was diagnosed in 45 (72.6 %) patients, and left-sided one - in 10 (16.1 %). Bilateral IH before surgery was diagnosed in 7 (11.3 %) children. For surgical interventions, we have used straight or 30° 5-mm laparoscope. Results and discussion. Among the advantages of laparoscopic techniques, and particularly PIRS method, there is the ability to detect failure of closure of the processus vaginalis with contralateral side. Thus, in 6 (9.7 %) patients, the expansion of the internal inguinal ring on the opposite side was visualized intraoperatively. Also, the advantage of this method is using a single optical port with the diameter of 3-5 mm and no need for laying on intracorporeal suturing. None of operated patients, when applying thread Ethibond* Excel 2-0, complained about postoperative discomfort in the area of postoperative node, which was placed subcutaneously in the inguinal area. In the study, IH recurrence was detected in 2 (3.2 %) boys. These patients also underwent reintervention using the PIRS technique. Conclusions. PIRS - a simple and efficient minimally invasive method for surgical correction of IH, which has a good cosmetic result. The application of laparoscopic method in the treatment of IH in children allows us to carefully examine the internal inguinal rings and, if necessary, to correct defects on both sides. The use of thread Ethibond* Excel 2-0 for suturing the inner ring of the inguinal canal is effective and provides optimal functional results. The risk of IH recurrence after surgery by PIRS method is a comparative in terms of risk of relapse after classical method surgery.